Abnormal grain growth in ultrafine grained Ni under high-cycle loading. (1st March 2022) - Barrios, Alejandro; Zhang, Yin; Maeder, Xavier; Castelluccio, Gustavo; Pierron, Olivier; Zhu, Ting
Abstract: Abnormal grain growth can occur in polycrystalline materials with only a fraction of grains growing drastically to consume other grains. Here we report abnormal grain growth in ultrafine grained metal in a rarely explored high-cycle loading regime at ambient temperature. Abnormal grain growth is observed in electroplated Ni microbeams with average initial grain sizes less than 640 nm under a large number of loading cycles (up to 10 9 ) with low strain amplitudes (< 0.3%). Such abnormal grain growth occurs predominantly in the family of grains whose <100> orientation is along the tensile/compressive loading direction. Micromechanics analysis suggests that the elastic anisotropy of grains dictates the thermodynamic driving force of abnormal grain growth, such that the lowest strain energy density of the <100> oriented grain family dominates grain growth. This work unveils a unique type of abnormal grain growth that may be harnessed to tailor grain microstructures in materials. Graphical abstract: Image, graphical abstract